DIGITAL CONVERGENCE AND VALUE CREATION: TVONE’S STRATEGIC ADAPTATION TO THE DIGITAL LANDSCAPE - Prihatmadi, Sekarseta (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2024)
In the wake of the Analog Switch Off (ASO) in Indonesia since November 2022, the traditional television industry faces significant challenges, including a decline in viewership and a fiercely competitive advertising market. With over 40 digital channels available in Jakarta alone, compared to just 11 national television stations previously, and the growing dominance of digital media, traditional broadcasters are compelled to adapt. This study focuses on tvOne, a conventional television broadcaster, and its strategic responses to these challenges. Our research methodology employs a qualitative approach in order to extract valuable and insightful information from highly knowledgeable sources. To achieve this, we have conducted interviews with seasoned policymakers in tvOne's business strategy, as well as with professionals working in the digital division. By doing so, we aim to obtain a comprehensive understanding of the subject matter at hand. This will enable us to present a comprehensive and accurate report that will benefit the industry as a whole. The analysis reveals how tvOne leverages media convergence to transform digital threats into opportunities for value creation. Specifically, it explores tvOne's use of news broadcast footage and digital platforms like YouTube to carve out new economic niches. This case study contributes to the understanding of how television stations can utilize technology advancements to enhance the value of their offerings. It offers valuable strategies and recommendations for broadcasters navigating the rapid technological evolution in the digital era, underscoring the importance of adaptation and innovation in sustaining relevance and competitiveness